A study on the provision of new static information signage in International Islamic University Malaysia, Gombak campus - Sahrir, Syazwani; Bachok, Syahriah; Mohamed Osman, Mariana (IIUM Press, 2015)
The study is on the provision of the new static information signage in International Islamic University Malaysia, Gombak campus